How do we judge our confidence? Differential effects of meta‐memory feedback on eyewitness accuracy and confidence. Issue 2 (23rd January 2020) - Iida, Ryosuke; Itsukusima, Yukio; Mah, Eric Y.
Summary: According to the cue–belief model, we assess confidence in our memories using self‐credibility cues that reflect beliefs about our memory faculties. We tested the influence of meta‐memory feedback on self‐credibility cues in the context of eyewitness testimony, when feedback was provided prior to "testifying" via a memory questionnaire (Experiment 1) and after an initial memory questionnaire but before participants had to retake it (Experiment 2). Participants received feedback (good score, bad score, or none) on a fictitious scale purported to predict eyewitness memory ability. Those given good score feedback before testifying were more confident (but no more accurate) than those given bad score feedback. Feedback also affected confidence (good increased and bad decreased) and accuracy (good increased) after testifying but only on leading questions. These differential effects of meta‐memory feedback on confidence for normal and leading questions are not explained by the cue–belief model. Implications for our confidence judgments are discussed.